Unmasking the unusual: a comprehensive case study of elephantiasis nostras verrucosa on an amputation stump - S., Praveena (International Journal of Research in Dermatology, 2025)
Elephantiasis nostras verrucosa (ENV) is a rare form of chronic lymphedema that causes progressive cutaneous hypertrophy. It can lead to severe disfiguration of body parts with gravity-dependent blood flow, especially the lower extremities. Various factors can cause obstruction of the lymphatic system and result in ENV. Clinically, ENV is characterized by nonpitting edema and superimposed hyperkeratotic papulonodules with a verrucose or cobblestone-like appearance. Elephantiasis nostras verrucosa can be very difficult to treat, and comprehensive, long-term studies on the management of elephantiasis are unfortunately lacking. A case of 24 years old obese male presented with verrucous growth at a distal part of stump of the left leg since 6 months associated with itching and oozing. Clinical examination revealed pink coloured indurated cobble-stone like papulonodules with overlying crusting. Histopathological examination revealed papillomatosis in epidermis and increased in thick walled capillaries and lymphatics in upper reticular dermis consistant with lymphedema with verrucosa nostra. Treatment with topical keratolytics along with compression stocking is advised. ENV occurring on an amputation stump is scarcely reported, leaving clinicians without clear diagnostic or therapeutic guidance. Timely diagnosis through clinical evaluation and histopathological correlation is essential to distinguish ENV from other verrucous dermatoses and neoplastic conditions. Due to the progressive and disfiguring nature of ENV, early recognition and intervention are crucial in preventing further morbidity. This report adds to the limited literature on atypical presentations of ENV and underscores the importance of individualized patient care.